2014
DOI: 10.2174/13816128113199990543
|View full text |Cite
|
Sign up to set email alerts
|

Folate Deficiency and Aberrant Expression of DNA Methyltransferase 1 were Associated with Cervical Cancerization

Abstract: DNA methyltransferase 1 (DNMT1) plays a significant role in maintaining DNA methylation. Aberrant DNA methylation is a recognized feature of human cancers and folate is directly involved in DNA methylation via one-carbon metabolism. Previous reports also have suggested that folate deficiency was associated with many cancers. The aim of the present study was to evaluate the effect of folate deficiency and aberrant expression of DNA methyltransferase 1 (DNMT1) on cervical cancerization. The expression of DNMT1 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Our previous studies have shown that low folate status was involved in the development of cervical cancer, 21 , 22 , 28 but the role of folate in the development of CIN is still unclear. To our knowledge, this is the first large-scale population study to investigate whether folate could be clinically associated with the development of CIN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies have shown that low folate status was involved in the development of cervical cancer, 21 , 22 , 28 but the role of folate in the development of CIN is still unclear. To our knowledge, this is the first large-scale population study to investigate whether folate could be clinically associated with the development of CIN.…”
Section: Discussionmentioning
confidence: 99%
“… 19 The high-risk areas of neural tube defects lie along the Taihang Mountains, as do the high-risk areas of cervical cancer. 20 Our previous findings indicated that low levels of folate might increase the risk of cervical cancer, 21 and further experiments in vitro have shown that increasing folate levels correlated with decreased cell proliferation and increased apoptosis in human cervical cancer cell lines. 22 However, it is not clear whether folate is involved in the development of CIN.…”
Section: Introductionmentioning
confidence: 92%
“…However, silencing of tumour suppressor miRNAs through hypermethylation of CpG islands in their promoter regions has also been a reason for carcinogenesis ( 20 , 21 ). Wang et al , in the year 2013 had reported about the role of DNMT1 in cervical cancer ( 22 ). From in vitro and in vivo studies performed it was established that low levels of serum folate and high expression of DNMT1 protein or mRNA were extensively related with cervical carcinogenesis.…”
Section: Epigenetic Control Of Cervical Cancermentioning
confidence: 99%
“…Screening for miRNAs that are differently profiled in both normal and cancer tissues might help to detect miRNAs involved in the pathogenesis of cancer. In addition to the role of miRNAs, DNA methyltransferases (DNMTs) also have been implicated in the development and progression of multiple forms of cancer, including cervical cancer [ 11 , 12 ]. It has been considered as a critical regulator for epigenetic processes of chemotherapy [ 13 ], and proved to be regulated by miR-148b in pancreatic cancer cell lines [ 14 ] and in non-small cell cancer cells [ 15 ].…”
Section: Introductionmentioning
confidence: 99%